How is it effective for farmers to adopt environmentally friendly cultivated land protection technology: a configurational perspective - Dong, Hao; Zhou, Hang; Wei, Jing; Chen, Tianqing; Wu, Xueying (Frontiers in Environmental Science, 2023)
The adoption of environmentally friendly farmland conservation techniques by farmers is an important way to effectively curb agricultural surface pollution and promote the conservation of farmland quality. Based on 425 farmers’ in-depth interview data, a fuzzy-set qualitative comparative analysis method was used to construct a psychological cognition (farmers’ awareness and willingness to participate)—external context (organizational linkages and government regulation)—behavioral effect model to reveal the conditional configuration and multivariate paths of psychological cognition and external contextual factors influencing farmers’ behavioral effects on the adoption of environmentally friendly farmland conservation technologies. The results show that individual behavioral decision factors do not influence the behavioral effects of farmers. The results show that individual behavioral decision factors are not necessary to drive the effective adoption of environmentally friendly farmland conservation technologies and that multiple decision factors interact to form three sets of configurations that enhance the behavioral effectiveness of farmers, summarized as the willingness-to-participate dominant model, the internal and external constraints dominant model, and the external context dominant model.